CCAFS science informs the Green Growth Policy in Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS and CIAT provided technical and policy recommendations on the land productivity component of the Colombian Green Growth Policy, which was launched in July 2018. The current National Development Plan states a focus on financial instruments for sustainable agricultural activities that include climate-smart innovation processes and technologies in line with the Green Growth Policy.